Clean and Green Street: Kolaborasi Warga dan Mahasiswa dalam Mewujudkan Lingkungan Jalan Bersih, Hijau, dan Berkelanjutan - Dian Tangkeallo; Theresyam Kabanga; Ferdi Ferdi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This community service activity aims to improve street cleanliness and encourage the use of home gardens to support a clean, healthy, and sustainable environment. The main problems faced by the community include low awareness of environmental cleanliness, the persistence of trash along the roads, and underutilized yards. The activity implemented a qualitative approach through field observations, community interviews, outreach, and direct mentoring. The community service activities included the Clean Friday program, the construction of neighborhood gates, the creation of flower pots from recycled materials, and the use of home gardens for vegetable cultivation. The results of the activities showed a significant improvement in street cleanliness, increased use of home gardens as productive spaces, and growing awareness and active participation of the community, particularly the younger generation, in environmental protection. Furthermore, this activity also strengthened the values of mutual cooperation and local wisdom, which align with the Tana Toraja Masero concept of clean, healthy, independent, and sustainable development. Thus, this community service activity contributes positively to creating a sustainable environment and improving the community's quality of life in a sustainable manner